ANALISIS PENGARUH PENGGUNAAN REFRIGERAN SEKUNDER DAN RETROFITTING TERHADAP KINERJA MINI FREEZER - , TRIAJI PANGRIPTO PRAMUDANTORO, Dr. Eng. Tri Agung Rohmat, B.Eng, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Small refrigeration unit systems, with a capacity compressor of under a half HP, commonly are used in small shops, ice cream shop or storage of products / frozen foods. Such systems generally use a direct expansion refrigeration systems without secondary refrigerant in which direct contact occurs between the evaporator and the product. The weakness of this system is the cabin temperature easily to change as effect of the cooling load from the outside or the environment. On the other hand there is a refrigeration system equipped with secondary refrigerants, propylene glycol mixed with water, which could minimize the effect of load from outside. Refrigeration system using secondary refrigerant commonly used in large units, such as to produce ice cube. The use of secondary refrigerant are aimed to maintain the temperature of the cabin for longer than a system using direct expansion. The ability to maintain temperature of the cabin longer results in smaller electrical energy consumption. The purpose of this research is to study the performance and electrical energy consumption as effect of variying primary refrigerant, expansion valve, and secondary refrigerant used in the system. The experiment was conducted on a mini freezer with dimension of 66 x 54.5 x 46.5 (cm) which is provided with two expansion devices, thermostatic expansion valve and cappilary tube, and some spaces that can be filled with secondary refrigerant. The results show that the consumption of electrical energy were decrease, in a system without a secondary refrigerant thes average of electrical energy consumption for a period of one hour were around 0.274 kWh while the system equipped with secondary refrigerant was 0.254 kWh. Performance of arefrigeration system with higher concentration of secondary refrigerant show better results with the average efficiency of about 78.6%. The results showed the influence of refrigerant retrofitting the electrical energy consumption savings were of about 11.3%. While the performance of refrigeration systems that used expansion device of thermostatic expansion valve type showed relatively similar results with a refrigeration system that used a capillary tube. The results show that the refrigeration system equipped with secondary refrigerant could be used as a substitute for direct expansion refrigeration system for a small capacity.